Tax Amnesty Effect On Tax Avoidance And Its Consequences On Firm Value (Empirical Study On Companies In Indonesia Stock Exchange) - Fadhila, Zati Rizka; Handayani, Rr Sri (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2019)
This study aims to examine the influence of tax amnesty on tax avoidance and it’s consequency on firm value and tax avoidance as intervening variable. Variables examined in this research consisted of tax amnesty measured with dummy variable, tax avoidance which measured with shot-run tax avoidance (CETR), and firm value measured using Tobins’ Q. The sample which is used in this research was extracted with using proportional sampling. After reduces with several criteria, 287 firms are determined as samples. The results showed that tax amnesty effect on tax avoidance, tax avoidance effect on tax amnesty, tax amnesty effect on firm value, and tax avoidance is not as intervening variable.